Dual targeting improves capture of ultrasound microbubbles towards activated platelets but yields no additional benefit for imaging of arterial thrombosis. Issue 1 (December 2017) - Günther, F.; Heidt, T.; Kramer, M.; Khanicheh, E.; Klibanov, A.; Geibel-Zehender, A.; Ferrante, E.; Hilgendorf, I.; Wolf, D.; Zirlik, A.; Reinöhl, J.; Bode, C.; et al.
Abstract Platelets can be found on the surface of inflamed and ruptured atherosclerotic plaques. Thus, targeting of activated platelets may allow for molecular imaging of vulnerable atherosclerotic lesions. We here investigated microbubbles (MB) functionalized with the selectin ligand sialyl Lewisa individually (MBsLea ) or dually with sLea and an antibody targeting ligand-induced binding sites of the activated GPIIb/IIIa receptor (MBDual ). Assessed byin vitro flow chamber, targeted MB exhibited increased adhesion to platelets as compared to MBControl . While MBsLea rolled slowly on the platelets' surface, MBDual enhanced the percentage of firm adhesion.In vivo, MB were investigated by ultrasound in a model of ferric chloride induced non-occlusive carotid artery thrombosis. MBsLea and MBDual revealed a higher ultrasound mean acoustic intensity than MBControl (p < 0.05), however MBDual demonstrated no additional increase in mean signal intensity as compared to MBsLea . The degree of carotid artery stenosis on histology correlated well with the ultrasound acoustic intensity of targeted MB (p < 0.05). While dual targeting of MB using fast binding carbohydrate polymers and specific antibodies is a promising strategy to support adhesion to activated platelets under arterial shear stress, these advantages seem not readily translatable toin vivo models.